2004
DOI: 10.1109/tac.2004.835398
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Backstepping Control of a Class of Uncertain Nonlinear Systems With Unknown Backlash-Like Hysteresis

Abstract: In this note, we consider the same class of systems as in a previous paper, i.e., a class of uncertain dynamic nonlinear systems preceded by unknown backlash-like hysteresis nonlinearities, where the hysteresis is modeled by a differential equation, in the presence of bounded external disturbances. By using backstepping technique, robust adaptive backstepping control algorithms are developed. Unlike some existing control schemes for systems with hysteresis, the developed backstepping controllers do not require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
284
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(287 citation statements)
references
References 6 publications
0
284
0
3
Order By: Relevance
“…By adding and subtracting the virtual control law φ 2 (e 1 , z 1 ) to (11) and defining an error variable as z 2 = e 3 − φ 2 (e 1 , z 1 ), (11) can then be represented as:…”
Section: Proposition Of Ebsmcmentioning
confidence: 99%
See 1 more Smart Citation
“…By adding and subtracting the virtual control law φ 2 (e 1 , z 1 ) to (11) and defining an error variable as z 2 = e 3 − φ 2 (e 1 , z 1 ), (11) can then be represented as:…”
Section: Proposition Of Ebsmcmentioning
confidence: 99%
“…Some nonlinear functions can be estimated using neural networks with a backstepping design scheme. Other robust backstepping control approaches for specific nonlinearities, such as system time delays [9], mismatched uncertainties [10], backlash-like hysteresis [11] and input uncertainties [12], were also developed to make the resulting system insensitive to model uncertainties and external disturbances. Moreover, in recent studies [13][14][15][16], it has been demonstrated that the backstepping controller design concept can be applied for different nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%
“…where the control gain β 0 =b 0 K q , and we consider ∆ q h = b 0 q h , due to hysteresis, a bounded disturbance input to the system, as has been done in Su et al [2000] and Zhou et al [2004]. From (13) and (14) we see that the hysteretic behavior is bounded by q h ∞ = b a .…”
Section: Controlmentioning
confidence: 99%
“…[19][20][21] However, the backstepping has trouble solving the 'explosion of complexity'. To solve this issue, by introducing a first-order filter at each recursive step of backstepping, the dynamic surface control is proposed to avoid the differentiation items on the virtual function.…”
Section: Introductionmentioning
confidence: 99%